Health-related physical fitness and physical activity in elementary school students - Weiyun Chen; Austin Hammond-Bennett; Andrew Hypnar; Steve Mason (BMC, 2018)
Abstract Background This study examined associations between students' physical fitness and physical activity (PA), as well as what specific physical fitness components were more significant correlates to being physically active in different settings for boys and girls. Methods A total of 265 fifth-grade students with an average age of 11 voluntarily participated in this study. The students' physical fitness was assessed using four FitnessGram tests, including Progressive Aerobic Cardiovascular Endurance Run (PACER), curl-up, push-up, and trunk lift tests. The students' daily PA was assessed in various settings using a daily PA log for 7 days. Data was analyzed with descriptive statistics, univariate analyses, and multiple R-squared liner regression methods. Results Performance on the four physical fitness tests was significantly associated with the PA minutes spent in physical education (PE) class and recess for the total sample and for girls, but not for boys. Performance on the four fitness tests was significantly linked to participation in sports/dances outside school and the total weekly PA minutes for the total sample, boys, and girls. Further, boys and girls who were the most physically fit spent significantly more time engaging in sports/dances and had greater total weekly PA than boys and girls who were not physically fit. In addition, the physically fit girls were more physically active in recess than girls who were not physically fit. Conclusions Overall, students' performance on the four physical fitness tests was significantly associated with them being physically active during PE and in recess and engaging in sports/dances, as well as with their total weekly PA minutes, but not with their participation in non-organized physical play outside school. Trial registration ClinicalTrials.gov ID: NCT03015337, registered date: 1/09/2017, as "retrospectively registered"